Mauritius : Report on the Observance of Standards and Codes (ROSC) Data Module. (IMF Staff Country Reports; Country Report ;, 2002)
This report assesses the quality of Mauritius' macroeconomic statistics and data dissemination practices as of July 2001. The assessment reveals that Mauritius meets the General Data Dissemination System recommendations for coverage, timeliness, and periodicity for most of the categories of macroeconomic data, although there are some important exceptions. Mauritius has prepared action plans to enhance statistical performance in a number of areas. Its statistical agencies have an institutional structure and considerable experience that supports data quality. Agencies demonstrate an awareness of quality as the cornerstone of statistical work.